Experimental Analysis of Watertightness Performance of Interfaces between Masonry and Steel Structures Subjected to Accelerated Aging - Alex de Freitas Bhering; Rayane Neves Franco; Mariana Araújo dos Santos; Lorena de Melo Sathler; Leonardo Gonçalves Pedroti; Humberto Varum; Gustavo de Souza Veríssimo; José Luiz Rangel Paes (Buildings, 2023)
Steel buildings often experience failure at the interfaces between their vertical exterior enclosure systems (VEESs) and structural elements. This phenomenon generates various pathological manifestations in steel buildings, resulting in the precocious decay of the structure and the diminishment of its service life. The treatment of these interfaces is essential for ensuring their proper performance and watertightness, and to protect the durability of the steel structure. This paper proposes a method for treating common interface joints between masonry and steel structures with the application of an EPDM (ethylene propylene diene monomer) elastomer membrane. The main goal of this building technique is to ensure the durability and watertightness of the interface’s joints when they are subjected to aging triggered by heat exposure and thermal shock. The experimental models tested consisted of a steel frame and a conventional masonry vertical enclosure system with ceramic blocks plastered with cement mortar. The models were subjected to ten cycles of heat exposure and thermal shock for the purpose of simulating accelerated aging, followed by a watertightness experiment that simulated the action of both rain and wind pressure. The interfaces between masonry and the steel structure proposed in this study allowed adequate differential movements between the parts, without damage to joints and masonry. Only small cracks were observed in the outer test region of all of the interfaces tested. In the regions of the joints treated with the EPDM membrane, no alterations were visible to the naked eye. During the cycles of the heat exposure and thermal shock test, the maximum relative horizontal displacements observed in the joints were 0.743 mm for vertical joints and 0.230 mm for horizontal joints, indicating the accurate reproduction of the behavior expected from an untied interface. The results obtained in the previously mentioned watertightness test showed that no humidity stains were found on the inner face of any of the specimens, even after the continuous application of a pneumatic pressure of 400 Pa for eight hours. Therefore, the results indicated satisfactory performance in terms of durability and watertightness in all evaluated cases, indicating that the application of an EPDM membrane can be effective in preventing water leaks in the interfaces between masonry and steel elements, thus contributing to ensuring the steel structure’s durability.